A Controller Design Researh Based on the Cloud Model - Feng Jie; Jingfang Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
A novel control structure model is proposed based on cloud model for the first time．The structure model is a nonlinear model in nature, and it can be composed of a group of uncertain reasoning rules easily．NonIinear mapping characteristics of cloud model is analysed in this sudy, and the design method of the intelligent controller is presented based on the structure model, and some simulation examples are showed．